Cancer-related thrombosis: impact of biological sex on the risk of rethrombosis and bleeding - Silvia García Adrián; Claudia Iglesias Pérez; Alberto Carmona-Bayonas; Laura Ortega Morán; Jaime Rubio Pérez; Purificación Martínez del Prado; Eva Martínez de Castro; Fernando Neria; Isaura Fernández Pérez; Marta García de Herreros; Marta Carmona Campos; Ignacio García Escobar; et al. (Haematologica)
Patients with cancer present a higher risk of rethrombosis and bleeding secondary to anticoagulant treatment than individuals without cancer. Given the lack of specific clinical trials, the decision regarding the optimal duration of treatment must consider multiple factors, including sex. The current study used data from the international, prospective TESEO Registry that includes consecutive patients diagnosed with cancer-associated thrombosis (CAT). Between July 2018 and December 2022, 2,823 patients were included in the TESEO Registry, 1,351 (48%) of whom were female. The most common venous thromboembolic event (VTE) in both sexes was pulmonary embolism (PE), with an incidence of 58.0% among men and 54.3% in women (p=0.045). After a median follow-up of 6.9 months (IQR, 1.9-14.4), the rethrombosis rate at the end of follow up was 10.0% in males and 15.0% in females (p=0.14). The location of the primary tumor in the gastrointestinal tract was associated with a greater risk of rethrombosis, whereas sex had no significant impact. Men presented twice as many major bleeds. Additional risk factors for major bleeding included situations of risk due to tumor site or thrombocytopenia, as well as the presence of active tumor bleeding at the time of VTE diagnosis. Overall survival was higher among women. Given the higher incidence of major bleeding among men, sex should be deemed a relevant factor when deciding on the duration of anticoagulant treatment in cancer patients.